Discovery and Structure–Activity Relationships of N‐Aryl 6‐Aminoquinoxalines as Potent PFKFB3 Kinase Inhibitors. (6th December 2018) - Boutard, Nicolas; Białas, Arkadiusz; Sabiniarz, Aleksandra; Guzik, Paweł; Banaszak, Katarzyna; Biela, Artur; Bień, Marcin; Buda, Anna; Bugaj, Barbara; Cieluch, Ewelina; Cierpich, Anna; Dudek, Łukasz; et al.
Abstract: Energy and biomass production in cancer cells are largely supported by aerobic glycolysis in what is called the Warburg effect. The process is regulated by key enzymes, among which phosphofructokinase PFK‐2 plays a significant role by producing fructose‐2, 6‐biphosphate; the most potent activator of the glycolysis rate‐limiting step performed by phosphofructokinase PFK‐1. Herein, the synthesis, biological evaluation and structure–activity relationship of novel inhibitors of 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐biphosphatase 3 (PFKFB3), which is the ubiquitous and hypoxia‐induced isoform of PFK‐2, are reported. X‐ray crystallography and docking were instrumental in the design and optimisation of a series of N‐aryl 6‐aminoquinoxalines. The most potent representative, N ‐(4‐methanesulfonylpyridin‐3‐yl)‐8‐(3‐methyl‐1‐benzothiophen‐5‐yl)quinoxalin‐6‐amine, displayed an IC50 of 14 nm for the target and an IC50 of 0.49 μm for fructose‐2, 6‐biphosphate production in human colon carcinoma HCT116 cells. This work provides a new entry in the field of PFKFB3 inhibitors with potential for development in oncology. Abstract : In a bind : Structure‐based design has led to the discovery of new, potent small‐molecule inhibitors of 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐biphosphatase 3 (PFKFB3) to regulate glycolytic flux and inhibit the proliferation of cancer cells. The binding of these new compounds was studied by means of X‐ray crystallography, allowing for the elucidation of structure–activity relationship elements.